Interobserver reliability of classifying shoulder calcific tendinopathy on plain radiography and ultrasound - A. Fernández-Bravo Rueda; B. Gutiérrez-San José; J. Fernández-Jara; A. Fernández-López; P. Núñez de Aysa; D. González-Martín; E. Calvo; M.D. Martín-Ríos (Revista Española de Cirugía Ortopédica y Traumatología)
Introduction: Shoulder calcific tendinopathy is a frequent cause of shoulder pain. Diagnosis is usually based on ultrasound (US) and/or X-ray. US is considered an inherently operator-dependent imaging modality and, interobserver variability has previously been described by experts in the musculoskeletal US. The main objective of this study is to assess the interobserver agreement for shoulder calcific tendinopathy attending to the size, type, and location of calcium analyzed in plain film and ultrasound among trained musculoskeletal radiologists. Material and methods: From June 2018 to May 2019, we conducted a prospective study. Patients diagnosed with shoulder pain related to calcific tendinopathy were included. Two different experienced musculoskeletal radiologists evaluated independently the plain film and the US. Results: Forty patients, with a mean age of 54.6 years, were included. Cohen's kappa coefficient of 0.721 and 0.761 was obtained for the type of calcium encountered in plain film and the US, respectively. The location of calcification obtained a coefficient of 0.927 and 0.760 in plain film and US, respectively. The size of the calcification presented an intraclass correlation coefficient (ICC) of 0.891 and 0.86 in plain film and US respectively. No statistically significant differences were found in either measurement. Conclusion: This study shows very good interobserver reliability of type and size measurement (plain film and US) of shoulder calcifying tendinopathy in experienced musculoskeletal radiologists. Resumen: Introducción: La tendinopatía calcificante de hombro es una causa frecuente de dolor de hombro. El diagnóstico suele basarse en la ecografía (US) y/o la radiografía. La ecografía se considera una modalidad de imagen inherentemente operador dependiente, y la discrepancia interobservador ha sido descrita previamente por expertos en ecografía musculoesquelética. El objetivo principal de este estudio es evaluar la concordancia interobservador para la tendinopatía calcificante del hombro atendiendo al tamaño, al tipo y a la localización del calcio analizado en la radiografía simple y la ecografía entre radiólogos musculoesqueléticos experimentados. Metodología: Entre junio de 2018 y mayo de 2019 se realizó un estudio prospectivo. Se incluyeron pacientes diagnosticados de tendinopatía calcificante de hombro sintomática. Dos radiólogos musculoesqueléticos experimentados evaluaron de forma independiente la radiografía simple y la ecografía. Resultados: Se incluyeron 40 pacientes, con una edad media de 54,6 años. Se obtuvo un coeficiente kappa de Cohen de 0,721 y 0,761 para el tipo de calcificación encontrada en la radiografía simple y la ecografía, respectivamente. La localización de la calcificación obtuvo un coeficiente de 0,927 y 0,760 en la radiografía simple y la ecografía, respectivamente. El tamaño de la calcificación presentó un coeficiente de correlación intraclase (CCI) de 0,891 y 0,86 en la película simple y la ecografía, respectivamente. No se encontraron diferencias estadísticamente significativas. Conclusiones: La concordancia interobservador en la medición del tipo y del tamaño de la calcificación en la tendinopatía calcificante de hombro entre radiólogos musculoesqueléticos experimentados es muy buena, tanto en la radiografía simple como en la ecografía.